2006
DOI: 10.1108/1525383x200600015
|View full text |Cite
|
Sign up to set email alerts
|

International Channels of Distribution: A Classification System for Analyzing Research Studies

Abstract: This paper presents a systematic method for classifying research on international channels of distribution, it is used to examine 79 articles published during an 18-year period (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005). Based on content analysis, each article is classified by its primary research framework. Two frameworks are identified: (1) structural -based on the economic and organizational aspects of international channels of distribution; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 100 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…QiaoLinx was designed to help executives bridge the cultural gap and facilitate the establishment of personal relationships. Their services differed significantly from channel partners (export brokers, sales representatives or distributors) who acted as third parties or intermediaries but did little to help in fostering business relationships (Ensign, 2006). Third party brokers also presented other problems such as selecting the right sales rep or distributor and negotiating a contract.…”
Section: Brian Addedmentioning
confidence: 99%
“…QiaoLinx was designed to help executives bridge the cultural gap and facilitate the establishment of personal relationships. Their services differed significantly from channel partners (export brokers, sales representatives or distributors) who acted as third parties or intermediaries but did little to help in fostering business relationships (Ensign, 2006). Third party brokers also presented other problems such as selecting the right sales rep or distributor and negotiating a contract.…”
Section: Brian Addedmentioning
confidence: 99%
“…Sales channel can be regarded as the process of transferring particular products or services from producers to consumers (El-Ansary and Stern, 1972). Ensign (2006) has suggested that how channel members perceive, build, and deal with relationships that exist within the channel are crucial. Makhura (2001), Dossa et al (2008), Millar and Photakoun (2008), Mertz et al (2009), Ampaire and Rothschild (2010) and Namonje-Kapembwa et al (2016), in their studies, have mentioned sales channels where animal producers feel it is relatively easier to access, participate, negotiate and sell.…”
Section: Sales Channel Conveniencementioning
confidence: 99%
“…A firm needs to address some basic distribution decisions in order to achieve its distribution objectives. In both domestic and international channel context, designing and managing channels of distribution are accepted as the two most fundamental and strategic decisions (see, among others, Ensign, 2006; Rangan et al , 1992; Rosenbloom et al , 1997). This is because well implemented design and management policies help the firm in the attainment of differential advantage (see Mehta et al , 2002; Pelton et al , 2002).…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%